Classical density functional theory and Monte Carlo simulation study of electric double layer in the vicinity of a cylindrical electrode. (19th July 2017) - Zhou, Shiqi; Lamperski, Stanisław; Sokołowska, Marta
Abstract: We have performed extensive Monte-Carlo simulations and classical density functional theory (DFT) calculations of the electrical double layer (EDL) near a cylindrical electrode in a primitive model (PM) modified by incorporating interionic dispersion interactions. It is concluded that (i) in general, an unsophisticated use of the mean field (MF) approximation for the interionic dispersion interactions does not distinctly worsen the classical DFT performance, even if the salt ions considered are highly asymmetrical in size (3:1) and charge (5:1), the bulk molar concentration considered is high up to a total bulk ion packing fraction of 0.314, and the surface charge density of up to 0.5 C m −2 . (ii) More specifically, considering the possible noises in the simulation, the local volume charge density profiles are the most accurately predicted by the classical DFT in all situations, and the co- and counter-ion singlet distributions are also rather accurately predicted; whereas the mean electrostatic potential profile is relatively less accurately predicted due to an integral amplification of minor inaccuracy of the singlet distributions. (iii) It is found that the layered structure of the co-ion distribution is abnormally possible only if the surface charge density is high enough (for example 0.5 C m −2 ); moreover, the co-ion valence abnormally influences the peak height of the first counter-ion layer, which decreases with the former. (iv) Even if both the simulation and DFT indicate an insignificant contribution of the interionic dispersion interaction to the above three 'local' quantities, it is clearly shown by the classical DFT that the interionic dispersion interaction does significantly influence a 'global' quantity like the cylinder surface-aqueous electrolyte interfacial tension, and this may imply the role of the interionic dispersion interaction in explaining the specific Hofmeister effects. We elucidate all of the above observations based on the arguments from the liquid state theory and at the molecular scale.